Chemistry of glucose and biochemical pathways of biological interest - Pischetsrieder, Monika (Peritoneal Dialysis International, 2000)
Glucose degradation, yielding GDPs, can take place in vivo or during heat treatment of glucose solutions. AGEs are formed from the interaction of D-glucose with reactive amino-acid side chains of proteins. Both GDPs and AGEs have been shown to impair cellular function. GDPs have additional damaging effects because they strongly promote AGE formation (as compared to D-glucose).
UnivIS-Import:2015-03-06:Pub.2000.nat.dchph.llmch.chemis
Keywords: 3-Deoxyglucosone; Advanced glycation end-products; Amadori product; Glucose degradation products